C1q deficiency in an Inuit family identification of a new class of C1q disease-causing mutations - Marquart, Hanne Vibeke (Clinical immunology (Orlando, Fla.), 2007)
C1q deficiency is a rare condition associated with a systemic lupus erythematosus (SLE)-like syndrome and recurrent infections. Here we present the molecular basis behind C1q deficiency in three sisters of Inuit origin. Initial examination for complement deficiency showed no function of the classical complement activation pathway in the patients; the lectin and alternative pathways were intact. No C1q or low molecular weight C1q was detected in sera and no anti-C1q autoantibodies were found. Sequencing of the C1q genes revealed a novel missense mutation (Gly-Arg) in codon 217 of the B chain. All sisters were homozygous for the mutation: both parents were heterozygous. None of 100 healthy controls carried the mutation. Our findings define a third class of molecular mechanisms behind C1q deficiency, where missense mutations cause a lack of detectable C1q-antigen in serum